Analisis Strategi Pengelolaan Keuangan Desa Dalam Meningkatkan Kesejahteraan Masyarakat Desa - Arya Ganang Prabowo; Dyah Palupiningtyas (Universitas Sains dan Teknologi Komputer, 2024)
The objective of this research is to examine the strategies employed in managing village finances to enhance community well-being in Jembrak Village, Semarang Regency. The research methodology involves a descriptive qualitative approach utilizing interviews, observations, and documentation for data collection. Findings reveal that the financial management strategy in Jembrak Village comprises planning, execution, administration, and accountability stages. Key factors impacting the success of village financial management include the proficiency of village officials, community engagement, oversight, and regulatory frameworks. Effective village financial management yields positive outcomes such as elevated per capita income, poverty reduction, enhanced education and healthcare standards, and improved access to essential infrastructure. Recommendations from the study emphasize the necessity of enhancing the competency of village officials, fostering community involvement, reinforcing supervision mechanisms, aligning regulations, and fostering collaboration between local and central governments in village financial management endeavors.